2007
DOI: 10.1038/sj.onc.1210897
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule cell-impermeant Hsp90 antagonist inhibits tumor cell motility and invasion

Abstract: Heat shock protein 90 (Hsp90) is a molecular chaperone that maintains function of numerous intracellular signaling nodes utilized by cancer cells for proliferation and survival. Hsp90 is also detected on the plasma membrane of tumor cells and its expression has been suggested to correlate with metastatic potential. Given the abundance and diverse functions of the intracellular pool of this protein, the precise contribution of cell surface Hsp90 to cell motility and tumor metastasis remains to be determined. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
182
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(189 citation statements)
references
References 30 publications
6
182
0
1
Order By: Relevance
“…Another inhibitor, geldanamycin (GA), when conjugated with FITC (GA-FITC) is cell-membrane impermeable, binding only cell surface HSP90 (Fig. 1B, Left) and inhibiting its functions but having no effect on cytosolic HSP90 (21,22). We found that GA but not GA-FITC blocked cross-presentation (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Another inhibitor, geldanamycin (GA), when conjugated with FITC (GA-FITC) is cell-membrane impermeable, binding only cell surface HSP90 (Fig. 1B, Left) and inhibiting its functions but having no effect on cytosolic HSP90 (21,22). We found that GA but not GA-FITC blocked cross-presentation (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Inhibition of Hop may have affected MMP-2 expression and activity through altering the activity of extracellular Hsp90. A study by Tsutsumi et al [22] using the non cell-permeable Hsp90 inhibitor, DMAG-N-oxide, reduced in vitro tumour cell invasion and migration and decreased melanoma lung metastasis in vivo. The monoclonal antibody (mAb) directed against Hsp90, mAb 4C5, inhibited melanoma cell invasion and significantly reduced metastasis in vivo by binding to surface Hsp90 as it is not internalised, further indicating an extracellular role for Hsp90 [23].…”
Section: Hop Co-immunoprecipitates With Mmp-2mentioning
confidence: 99%
“…42 DMGA-N-oxide, a novel cell-impermeable Hsp90 inhibitor, was reported to show a dramatic impact on the metastatic phenotype of the lung colonization of melanoma cells and be related to the hepatotoxic property of benzoquinone ansamycins. 43 The O-carbamoylmethyloxime derivative of radicicol, KF25706, inhibits v-Src-and k-Ras-activated signaling. 44,45 Macbecin 46 and its non-quinone compound that target Hsp90 have been reported, 47 indicating that the quinone moiety of macbecin is not a prerequisite for Hsp90 inhibition.…”
Section: Hsp90 Inhibitors Are Promising For Cancer Therapymentioning
confidence: 99%